'Know Thyself'? Borderlinearity in Alice Munro's 'Dimension'. (2nd January 2017) - Disney, Dan
ABSTRACT: In Alice Munro's short story, 'Dimension, ' the protagonist Doree shifts through the nightmare aftermath of her children's murder. Her husband Lloyd, the murderer, has been incarcerated in a facility for the criminally insane, and his madness can be read as 'clearly distinguishable from those understood as neurotic or psychotic'. 1 Lloyd demonstrably endures some kind of ' narcissistic crisis ' (Kristeva, 14) and, his drives and impulses disordered, his actions are regulated instead by 'repugnance, disgust, abjection' (Kristeva, 11). Munro begins her story with Doree making a third trip to visit her antagonist; the first two he has 'refused to see her', 2 and at work within these narrative structures are spatial, psychic, and potentially cathartic drives. Doree explores a boundary containing a monstrous presence, circling as if locked in the afterwardsness of repetition compulsion. She is at once searching for a means to anesthetise her trauma while seeking for ways to shatter those imago her much older husband has so expertly (and toxically) constructed.